2019
DOI: 10.1002/ima.22353
|View full text |Cite
|
Sign up to set email alerts
|

Voxel selection framework based on meta‐heuristic search and mutual information for brain decoding

Abstract: Visual stimulus decoding is an increasingly important challenge in neuroscience. The goal is to classify the activity patterns from the human brain; during the sighting of visual objects. One of the crucial problems in the brain decoder is the selecting informative voxels. We propose a meta‐heuristic voxel selection framework for brain decoding. It is composed of four phases: preprocessing of fMRI data; filtering insignificant voxels; postprocessing; and meta‐heuristics selection. The main contribution is bene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…(Algo. 1) illustrates the proposed voxel selection method [26]. For instance, in the Haxby dataset [23], there are eight categories of objects where the duration and time of repetitions, TR, are 24 and 2.5 Seconds, respectively.…”
Section: B Voxel Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Algo. 1) illustrates the proposed voxel selection method [26]. For instance, in the Haxby dataset [23], there are eight categories of objects where the duration and time of repetitions, TR, are 24 and 2.5 Seconds, respectively.…”
Section: B Voxel Selectionmentioning
confidence: 99%
“…Moreover, voxels usually contain noise and irrelevant information; consequently, many pre-processing routines like normalization, scaling, and voxel selection would be required to conduct activity localization. Some exciting studies on the voxel selection problem can be found in [24]- [26]. Various multiview (MV) learning applications in the real world exist due to several features that describe an object.…”
Section: Introductionmentioning
confidence: 99%